Subjective Time : The Philosophy, Psychology, and Neuroscience of Temporality - Arstila, Valtteri, 1974- (Book collections on Project MUSE., 2014)
Our awareness of time and temporal properties is a constant feature of conscious life. Subjective temporality structures and guides every aspect of behavior and cognition, distinguishing memory, perception, and anticipation. This milestone volume brings together research on temporality from leading scholars in philosophy, psychology, and neuroscience, defining a new field of interdisciplinary research.